Representasi Romantisme dalam Puisi “Aku Ingin” Karya Sapardi Djoko Damono - Fitria Ika Farizha; Dwi Wahyu Candra Dewi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Literature as a medium to express ideas, emotions, or social problems that occur. This study aims to reveal the representation of romance in the poem